Organizational Behavior (Open textbook library., 2019)
This OpenStax resource aligns to introductory courses in Organizational Behavior. The text presents the theory, concepts, and applications with particular emphasis on the impact that individuals and groups can have on organizational performance and culture. An array of recurring features engages students in entrepreneurial thinking, managing change, using tools/technology, and responsible management; furthermore, the unique chapter on Social Media and Communication contextualizes the importance and implications of various platforms and communications methods.